Reconstructing the weather on Mars at the time of the MERs and Beagle 2 landings - Montabone, L; Lewis, SR; Read, P; Withers, P (2006)
We reconstruct the temperature, wind and density structure of the atmosphere on Mars from the surface to 120 km altitude at the time of the landing of the two NASA Mars Exploration Rovers (MER), and ESA's "Beagle 2." This reconstruction is based on an assimilation of temperature and dust opacity observations from the Thermal Emission Spectrometer aboard the Mars Global Surveyor spacecraft into a general circulation model of the Martian atmosphere and, for the case of the MERs, on retrievals of temperature and density profiles from accelerometer data. For all landers, the reconstruction of the atmospheric state is compared with the climatological state predicted by the European Mars Climate Database (EMCD) for two different prescribed dust scenarios, with added large- and small-scale variability. This comparison exhibits good agreement for all three landers within the modeled variability, confirming a posteriori the accuracy of the climate forecasts by the EMCD. Copyright 2006 by the American Geophysical Union.